MHD mixed convection of nanofluid filled partially heated triangular enclosure with a rotating adiabatic cylinder - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Science Bv, 2014)
MHD mixed convection of Cu-water nanofluid filled triangular enclosure with a rotating cylinder is investigated numerically. A partial heater is added on the left vertical wall of the cavity and the right inclined wall is kept at constant temperature. Other walls of the triangular cavity and cylinder surface are assumed to be adiabatic. The governing equations are solved using the finite element method. The effects of the Grashof number, Hartmann number, angular rotational speed of the cylinder and volume fraction of the nanoparticle on fluid flow and heat transfer are investigated numerically. The second law of thermodynamics is also applied to the flow and heat transfer corresponding to different combinations of parameters. It is observed that with increasing the Hartmann number the total entropy generation, local and averaged heat transfer decrease. Averaged Nusselt number increases with the Grashof number. Averaged heat transfer and total entropy generation increase with increase in the angular rotational speed of the cylinder. 50.4% and 37.4% of heat transfer enhancements are obtained for omega = 20 and omega = -20 compared to motionless cylinder omega = 0. Heat transfer and total entropy generation increase as the solid volume fraction of nanoparticle increases. (C) 2014 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: MHD flow; Entropy; Nanofluid; Finite element method